Meta-Analysis the Effect of Postpartum Exercise on Uterine Fundal Height - Istiqomah, Anisa Ikhlasani Nur; Murti, Bhisma; Adriani, Rita Benya (Journal of Maternal and Child Health, 2024)
Background: Postpartum is a period that is at risk of causing complications and often contributes to maternal mortality rates in Indonesia. One of the causes of maternal death is an irregularity in the involution process, resulting in the risk of postpartum hemorrhage. This study aims to analyze and estimate the influence of postpartum exercise on reducing TFU in postpartum mothers. Subjects and Method: This study is a systematic review and meta-analysis. Search for articles through journal databases including: Google Scholar, PubMed, and Springer Link by selecting articles published from 2013 to February 2023. The population in the study was postpartum mothers with intervention in the form of postpartum exercise, comparison in the form of no intervention or no postpartum exercise, and the outcome is a decrease in TFU. The keywords used were (effect OR Influence) AND (“Parturition Gymnastics” OR “Postpartum Gymnastics” AND “fundal height” OR “decline of fundal height” OR “high uterine fundus” OR “Symphysial fundal height” OR “SFH” OR TFU”) AND (postpartum). The inclusion criteria were full paper articles using the Randomized Controlled Trial (RCT) research method, the analysis results used the Mean SD value, the intervention provided was postpartum exercise, the research subjects were postpartum mothers, with an outcome of decreasing TFU. Articles were collected using PRISMA flow diagrams and analyzed using the Review Manager 5.3 application. Results: Meta-analysis of 6 articles showed that postpartum exercise has an effect on reducing TFU in postpartum mothers by 0.46 units, which was higher than other interventions or no intervention, but this was not statistically significant. (SMD -0.46; 95% CI= -1.99 to 1.07; p=0.550). Conclusion: Postpartum exercise has an effect on reducing TFU in postpartum mothers.